2000
DOI: 10.1006/viro.1999.0178
|View full text |Cite
|
Sign up to set email alerts
|

Proline Residues in the HIV-1 NH2-Terminal Capsid Domain: Structure Determinants for Proper Core Assembly and Subsequent Steps of Early Replication

Abstract: Recent analyses suggest that the p24 capsid (p24(CA)) domain of the HIV-1 group-specific antigen (Gag) may be divided into two structurally and functionally distinct moieties: (i) an amino-terminal portion, previously shown to bind the cellular chaperone cyclophilin A, and (ii) a carboxy-terminal domain, known to contribute to the interaction of the Gag and Gag-Pol precursors during the early assembly process. In order to gain deeper insight into the role of the amino-terminal domain of the p24(CA) protein dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
101
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 67 publications
8
101
0
Order By: Relevance
“…However, the relevance of these findings to HIV remains unclear; there are significant differences in the architectures of HIV and RSV cores, suggesting that these capsids may mediate different functions during infection or may interact differently with host cell factors following delivery into the cytosol. In a recent study by Fitzon et al (14), mutagenesis of proline residues in HIV-1 CA led to defects in core stability, which correlated with reduced infectivity, similar to the effects observed in our study.…”
Section: Vol 76 2002 Regulated Disassembly Of the Hiv-1 Core 5673supporting
confidence: 90%
See 1 more Smart Citation
“…However, the relevance of these findings to HIV remains unclear; there are significant differences in the architectures of HIV and RSV cores, suggesting that these capsids may mediate different functions during infection or may interact differently with host cell factors following delivery into the cytosol. In a recent study by Fitzon et al (14), mutagenesis of proline residues in HIV-1 CA led to defects in core stability, which correlated with reduced infectivity, similar to the effects observed in our study.…”
Section: Vol 76 2002 Regulated Disassembly Of the Hiv-1 Core 5673supporting
confidence: 90%
“…Alternatively, the mutants may be defective for nuclear transport or integration of the provirus. Consistent with the latter hypothesis, other groups have reported CA mutations that are competent for second-strand transfer yet show defects in two-LTR circle formation, a marker of HIV-1 nuclear import (8,14). Further analysis of the unusual phenotype of the P38A and Q63A/Q67A mutants may reveal additional roles for CA during HIV-1 infection.…”
Section: Vol 76 2002 Regulated Disassembly Of the Hiv-1 Core 5673mentioning
confidence: 58%
“…The detailed mechanism of how cyclophilin A promotes HIV-1 replication is not understood, although several mechanisms have been discussed in recent years (5,6,22,23,28,30,(43)(44)(45). In light of the CA N ͞CypA cocrystal structure showing CA G89-P90 bound exclusively in the trans conformation (22), models depicting CypA as having a chaperone role in HIV-1 virulence have been suggested (28).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the N-terminal β-hairpin of CA destabilizes the immature lattice and facilitates the formation of mature capsid (39,40). To explore the formation of the N-terminal β-hairpin of CA in real-time and to probe other conformational changes that take place in ΔGag upon ordered proteolytic cleavage by HIV-1 protease, 1 H-15 N TROSY spectra of ΔGag were recorded at a series of time points in the presence of a minute amount of HIV-1 protease (Fig.…”
Section: Significancementioning
confidence: 99%